Social context during moral decision-making impacts males more than females - Pilcher, June J.; Smith, Phillip D. (Frontiers in Psychology, 2024)
Moral judgments are often viewed as the outcome of affective and deliberative processes that could be impacted by social factors and individual characteristics. The purpose of this study was to examine the interaction between gender and social context on moral judgment. Participants included 315 undergraduate students (67.3% female). The participants completed the Moral Decision-Making Task while seated at row tables facing the front of the room or round tables facing other participants. The results indicated that males responded in a more utilitarian manner (harm one to save five) than females for moral impersonal (MI) and moral personal (MP) dilemmas regardless of seating arrangements. When seated at round tables, all participants were more likely to respond deontologically (cause no harm) to the moral impersonal dilemmas. In addition, we calculated a moral reasoning difference score for each participant as the difference between the MI and MP scores to represent additional reactivity due to the idea of taking direct action. The moral reasoning difference score was consistent for females but indicated a more deontological response from males at round tables and a more utilitarian response from males at row tables. These results suggest that males are more utilitarian than females and are more likely to be influenced by social context when responding to moral dilemmas. More broadly, the current results indicate that moral judgments are affected by social context particularly in males in ways that have not been incorporated in many models of moral decision making.